Pathways for integrating socially responsible public procurement in municipalities - Maximilian Müngersdorff; Tim Stoffel (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
Public procurement expenditures of European Union (EU) member states are enormous, accounting for approximately 14 per cent of value creation in the EU. In many European countries, municipalities are responsible for a large share of these expenditures, as is the case in Germany. By integrating sustainability criteria in tenders for goods, works and services, municipalities can significantly contribute to Sustainable Development Goal (SDG) 12 of the 2030 Agenda for Sustainable Development, which is to ensure sustainable consumption and production patterns. Sustainable public procurement (SPP) practices are, however, the exception rather than the rule. While environmental criteria are increasingly considered, social standards have thus far been considered far less in public tenders. Thus, we analysed what could be done to support the implementation of Socially Responsible Public Procurement (SRPP) practices in German municipalities. Our empirical evidence shows that there is no gold standard for implementing SRPP in municipal contexts. Figure 1 presents a map with different entry points from which practitioners and policy-makers may embark on fitting pathways. We recommend measures in the following three dimensions. Regulatory dimension Regulations and their 'translation' for administrative bodies should be ambitious and clear. The regulatory framework on the municipal level should clearly specify how SPP is introduced and implemented, especially by defining concrete SPP goals and translating goals and policies for civil servants. Institutional dimension The basis for effective SPP measures is a strategic procurement organisation. Municipal stakeholders may take action in three areas to make procurement organisation more strategic. First, decision-makers can attach a higher value to procurement as an instrument to realise the strategic goals of the municipality. Second, a huge variety of procurement instruments is applicable to support this value shift. Third, due to the decentralised procurement structures in municipalities, coordination and communication between departments and persons should be streamlined, or municipal procurement should become more centralised. Individual dimension Information and capacity building should be offered to all stakeholders. In order to adjust regulatory and institutional conditions for effective SRPP implementation, support from administration and political decision-makers on all levels is a prerequisite. Providing customised information and offering capacity building can raise the level of support. In this regard, SRPP is most likely to be achieved when specific staff is assigned responsibility for its implementation. Based on insights from German municipalities, this paper outlines further success factors and underlying triggers to utilise public procurement in the transformation towards sustainability.
Keywords: 330